Isles of the dead? : the setting and function of the Bronze Age chambered cairns and cists of the Isles of Scilly - Sawyer, Katharine (Archaeopress archaeology., 2015)
The number and density of megalithic chambered cairns in the Isles of Scilly, a tiny archipelago that forms the most south-westerly part of the British Isles, has been remarked upon since the 18th century. 'Isles of the Dead?' examines these sites, generally known as entrance graves, and the associated cist graves. Their physical structure and contents, as well as their landscape setting, orientation and inter-visibility, are discussed.